2022
DOI: 10.3390/ijerph19031708
|View full text |Cite
|
Sign up to set email alerts
|

Does a Recycling Carbon Tax with Technological Progress in Clean Electricity Drive the Green Economy?

Abstract: The environmental issue is a significant challenge that China faces in leading the development of the green economy. In this context, reducing CO2 emissions is the key to combatting this problem. Taking the 2017 social accounting matrix (SAM) as the database and combing macroeconomic parameters from previous studies, this article constructed the environmentally computable general equilibrium (CGE) model as an analytical model to analyze the economic–environmental–energy impacts of recycling carbon tax with tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…To sum up, companies with good carbon performance will bring the following positive effects: Firstly, the better the carbon performance of an enterprise, the more positive signals it sends to the outside world that its development is in line with the current economic situation, establishing a good corporate image that responds positively to the national policy and strengthening the confidence of investors. Secondly, good carbon performance indicates that the company has an irreducible advantage in terms of environmental cost, which improves the competitive advantage of the company’s products and sustainable development ( Liu et al, 2022 ). Zhu and Zhang (2022) believe that energy enterprises focusing on environmental performance can optimize resource allocation and promote enterprise development.…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%
“…To sum up, companies with good carbon performance will bring the following positive effects: Firstly, the better the carbon performance of an enterprise, the more positive signals it sends to the outside world that its development is in line with the current economic situation, establishing a good corporate image that responds positively to the national policy and strengthening the confidence of investors. Secondly, good carbon performance indicates that the company has an irreducible advantage in terms of environmental cost, which improves the competitive advantage of the company’s products and sustainable development ( Liu et al, 2022 ). Zhu and Zhang (2022) believe that energy enterprises focusing on environmental performance can optimize resource allocation and promote enterprise development.…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Dagar et al (2022) suggested that environmental degradation will be reduced in the long run if real GDP growth moves towards greener (Qiu et al, 2018), more technologically advanced, and more environmentally friendly areas. Therefore, they proposed that under certain conditions, environmental taxes will not negatively impact enterprises (Adamou et al, 2012;Liu et al, 2022). Feng et al (2022) proved the existence of a double dividend effect in China under the low-carbon tax policy.…”
Section: Introductionmentioning
confidence: 99%
“…11 with 𝑊 * * − 𝑊 * = [𝑎(2𝑟 − 𝑏)] 2 /[(3𝑟 + 𝑏 + 2𝑔)(𝑟 + 2𝑏 + 2𝑔) 2 ] ≥ 0, if the gap between 𝑡 * * 𝑎𝑛𝑑 𝑡 * is bigger when 𝑊 * * 𝑎𝑛𝑑 𝑊 * has big gap also. For Proposal 3, one may refer to Liu et al[31] who find that a carbon tax can generate comprehensive effects on promoting economic development,…”
mentioning
confidence: 99%